From Aches to Answers: Understanding and Managing Hip Joint Issues in Kids - Rutkowski, Wojciech; Salwa, Adam; Gajdzińska, Natalia; Rostkowska, Weronika; Rzepka, Maciej; Sztuba, Karolina; Puchała, Justyna; Rymaszewska, Katarzyna; Starzomska, Dominika; Basiura, Karolina (Quality in Sport, 2024)
Introduction: Joint pain is a prevalent concern among pediatricians, orthopedists, and general practitioners, affecting up to 50% of children during childhood. The hip joint is particularly vulnerable, with degenerative diseases of the hip joints (DDHJ) being the leading cause of pediatric orthopedic visits. Various conditions, such as developmental dysplasia of the hip (DDH), Legg-Calve-Perthes Disease (LCPD), and slipped capital femoral epiphysis (SCFE), contribute to the spectrum of hip joint disorders in children. Material and methods: We have gathered the available materials and scientific reports, analyzing and summarizing them in a single study. Aim of study: This study aims to explore the etiology, diagnosis, and management of hip joint pain in children, focusing on DDH, LCPD, SCFE, and other related conditions. By examining the risk factors, clinical presentations, and current treatment strategies, the study seeks to enhance the understanding and early detection of these disorders, ultimately improving patient outcomes. Conclusion: Hip joint pain in children encompasses a broad differential diagnosis, ranging from self-limiting conditions like transient synovitis to serious disorders such as septic arthritis and JIA. Early identification and appropriate management of conditions like DDH, LCPD, and SCFE are crucial in preventing long-term complications. While physical activity is generally safe, intense exercise may increase the risk of musculoskeletal pain. A multidisciplinary approach, supported by further research, is essential for effective pain management and treatment optimization in pediatric patients.